Penggunaan Algoritma Profile Matching Untuk Perekrutan Karyawan - Fadilah, Novian; Amini, Safrina (LPPM UNIKA Santo Thomas Medan, 2020)
The success of a company is located on how to manage the human resources it owns. The proper management of resources and really appropriate employee field expertise is mandatory. To get a truly qualified human resources then it is necessary to do the recruitment of employees who actually comply with the operational standards of procedures. Inappropriate employee recruitment process will result in employees with poor performance and not as expected by the company. Assessment of prospective employees test results sometimes with certain prospective employees to harm the company. To overcome the problem then this research using profile matching method with the result of the research in the form of each prospective employees. Leaders can see the value of each prospective employee and can make a decision